LBJ's American promise : the 1965 voting rights address - Pauley, Garth E., 1971- (Library of presidential rhetoric., 2007)
Though Lyndon Johnson developed a reputation as a rough-hewn, arm-twisting deal-maker with a drawl, at a crucial moment in history he delivered an address to Congress that moved Martin Luther King Jr. to tears and earned praise from the media as the best presidential speech in American history. Even today, his voting rights address of 1965 ranks high not only in political significance, but also as an example of leadership through oratory.